Engendering change: Feminist considerations of online conferencing as a safe space in the narratives of South Africa women academics during COVID-19 - Parry, B. R.; Moodley, J. K.; Masisi , I. (South African Journal of Higher Education, 2024)
The digitisation of education that has deliberately reformed the pedagogical practices of tertiary education in the 21st century, rapidly transformed all aspects of academia during the COVID-19 pandemic. Academic conferences, as traditional sites of embodied knowledge production, were also impacted and virtual conferences were quickly adopted as socially responsible alternatives. As a component of contemporary academic work, conferencing is meant to foster networks of community and support deep learning but are most often criticised as sites that reproduce prevalent discriminatory academic hierarchies. The most common observations in gender analysis of conferencing report on inequalities of representation and the absence of women in key roles. As organisers of the Southern African Student Psychology Conference (SASPC), we explore our experiences organising our first online conference in the context of the pandemic. Unfortunately, very few researchers have considered the representative space of online forms of conferencing, and to date none reflect the experiences of women academics from South Africa. This article aims to extend these examinations of the gendered nature of academic conferencing by utilising Empowerment Theory (ET) to understand narrative reflections from three women academics and organisers of an online Southern African conference. Collaborative Autoethnography (CAE) served as a critical emancipatory tool for collectively gathering counter stories of our internalised oppression as marginalised women academics. Consequently, this article explicates the gendered dynamics of academia, as well as sustainable pedagogical possibilities for change that is engendered by technology through online spaces as important sites of agency and resistance.